Transgenesis enables mapping of segmental ganglia in the leech Helobdella austinensis - Kuo, Dian Han (2024)
The analysis of how neural circuits function in individuals and change during evolution is simplified by the existence of neurons identified as homologous within and across species. Invertebrates, including leeches, have been used for these purposes in part because their nervous systems comprise a high proportion of identified neurons, but technical limitations make it challenging to assess the full extent to which assumptions of stereotypy hold true. Here, we introduce Minos plasmid-mediated transgenesis as a tool for introducing transgenes into the embryos of the leech Helobdella austinensis (Spiralia; Lophotrochozoa; Annelida; Clitellata; Hirudinida; Glossiphoniidae). We identified an enhancer driving pan-neuronal expression of markers, including histone2B: mCherry, which allowed us to enumerate neurons in segmental ganglia. Unexpectedly, we found that the segmental ganglia of adult transgenic H. austinensis contain fewer and more variable numbers of neurons than in previously examined leech species.